Pemahaman Pencatatan Akuntansi pada Pelaku UMKM di Tangerang Selatan - Silvia Suka; Gabriela Eklesia Robot; Ani Rakhmanita (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This research reveals the financial records of culinary business MSMEs in the South Tangerang area by tracing how they carry out financial records in their businesses which are still running today. This research helps to find out how research subjects interact in managing their finances, helps understand the views, attitudes and behavior of MSMEs towards financial reports for the sustainability of their business. The Status Quo theory is used by researchers to understand and analyze the situation of MSME actors regarding accounting understanding. Data was collected through semi-structured interviews with 20 MSME actors in the culinary sector and then analyzed using a qualitative approach. The research findings show that the majority of MSMEs have not recorded their finances optimally. They still use traditional methods such as recording sales manually and do not meet financial accounting standards (SAK EMKM). The research recommendation is that MSME players need to improve their ability to carry out good and correct financial records for business continuity. The role of government and academics is needed to provide understanding and knowledge for MSMEs in the South Tangerang region, this can take the form of training on basic financial accounting, and implementing a simple recording system with the help of simple software